2017
DOI: 10.1007/978-3-319-70290-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Network Models in Cyber Security: A Systematic Review

Abstract: Abstract. Bayesian Networks (BNs) are an increasingly popular modelling technique in cyber security especially due to their capability to overcome data limitations. This is also exemplified by the growth of BN models development in cyber security. However, a comprehensive comparison and analysis of these models is missing. In this paper, we conduct a systematic review of the scientific literature and identify 17 standard BN models in cyber security. We analyse these models based on 8 different criteria and ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…In the context of computer science and information/cyber security, there are systematic reviews performed (Yli-Huumo et al, 2016;Agyepong et al, 2019;Chockalingam et al, 2017). A meta-analysis, however, builds on top of a systematic review and uses statistic methods to quantitatively pool and summarise the results of these studies (Akhter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of computer science and information/cyber security, there are systematic reviews performed (Yli-Huumo et al, 2016;Agyepong et al, 2019;Chockalingam et al, 2017). A meta-analysis, however, builds on top of a systematic review and uses statistic methods to quantitatively pool and summarise the results of these studies (Akhter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we conducted a systematic literature review of BN models in cyber security (Chockalingam et al 2017). In that study, we identified 17 standard BN models in cyber security based on the review methodology we adopted.…”
Section: Related Workmentioning
confidence: 99%
“…However, they are also not shareable due to the sensitivity of data. Therefore, we relied on expert knowledge which is one of the predominant data sources utilised to construct DAGs and populate CPTs especially in domains where there is a limited availability of data like cyber security (Chockalingam et al 2017). Furthermore, expert knowledge is substantive information on a specific domain based on the system knowledge that is not commonly known by others (Martin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, BN is not easy-to-use for brainstorming with domain experts as it could be time-consuming to explain the notion of BN and also to change its structure instantly based on discussions during brainstorming sessions. Notably, expert knowledge is one of the predominant data sources utilised to build BN structure with appropriate variables especially in domains where there is a limited availability of data like cyber security [40]. Therefore, our framework would be incomplete without an effective method for knowledge elicitation.…”
Section: Combining Bayesian Network and Fishbone Diagramsmentioning
confidence: 99%
“…Once the fishbone diagram is translated to a corresponding BN model, the quantitative part of the BN should be populated. Due to limited data availability, expert knowledge is the predominant data source used to populate CPTs of BNs in cyber security [40]. In our work, we did not investigate whether fishbone diagrams could be used as a means to elicit probabilities from experts as our main objective is to elicit appropriate variables in the construction of the BN structure for the considered problem.…”
Section: Fig 7 Fishbone Diagram Examplementioning
confidence: 99%